Challenges of motherhood in adolescent girls - Rajoriya, Mohini; Kalra, Ruchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: National Family Health Survey (NFHS)-3 revealed that 16% of women, aged 15-19 years, have already started childbearing of them urban were 8.7% and rural were 19.1%. Teenage pregnancy is of serious concern because maternal age plays a significant role in adverse outcome and complications of pregnancy. The study was done to find out incidence and analyse the maternal, foetal outcome in adolescent pregnancy. Methods: The study was conducted at People’s College of Medical Sciences and Research Centre, Bhopal from January 2010 to July 2013. All cases of teenage pregnancy who delivered during study period were analysed for age distribution, mode of delivery, indications for caesarean section, complications and neonatal weight. Results: 78 adolescent girls delivered during study period which was 2.1% of total deliveries. 78% were of age group 19 years, 18 % of cases were of 18 years of age 2.5% cases were of 17 years and 1.28% of case 14 years. 90% were primigravida. Total pre-term deliveries were 13% of the all adolescent deliveries. 46% delivered by caesarean section. Majority of caesarean sections were done for cephalo-pelvic disproportion (50% cases) followed by foetal distress (22%). 52% of cases had baby weight more than 2.5 kg. 35% of cases had weight between 2 kg and 2.5 kg and 13% of cases had weight less than 2 kg. PIH was found in 32% of cases, Anaemia and IUGR was present in 29% of cases. PPH occurred in 12.80% cases. Conclusions: In teenage pregnancy cesarean section rate was high (46%). PIH, anemia and IUGR were the associated complications. So we should best aim to reduce the incidence of teenage pregnancy, not only to minimize the adverse outcomes on young mothers but also to limit the family-size by providing adolescent friendly health services.